Association between BRCA2 alterations and intraductal and cribriform histologies in prostate cancer. (April 2021) - Lozano, Rebeca; Salles, Daniela C.; Sandhu, Shahneen; Aragón, Isabel M.; Thorne, Heather; López-Campos, Fernando; Rubio-Briones, José; Gutierrez-Pecharroman, Ana M.; Maldonado, Laneisha; di Domenico, Tomas; Sanz, Alejandro; Prieto, Juan D.; et al.
Abstract: Background: Intraductal (IDC) and cribriform (CRIB) histologies in prostate cancer have been associated with germline BRCA2 (gBRCA2) mutations in small retrospective series, leading to the recommendation of genetic testing for patients with IDC in the primary tumour. Patients and methods: To examine the association of gBRCA2 mutations and other tumour molecular features with IDC and/or cribriform (CRIB) histologies, we conducted a case–control study in which primary prostate tumours from 58 gBRCA2 carriers were matched (1:2) by Gleason Grade Group and specimen type to 116 non-carriers. Presence/absence of IDC and CRIB morphologies was established by two expert uropathologists blinded to gBRCA2 status. Fluorescent in-situ hybridization (FISH) and next-generation sequencing (NGS) were used to detect BRCA2 alterations, PTEN deletions and TMPRSS2-ERG fusions. Chi-squared tests were used to compare the frequency of IDC and CRIB in gBRCA2 carriers and controls and to assess associations with other variables. Logistic regression models were constructed to identify independent factors associated with both histology patterns. Results: No significant differences between gBRCA2 carriers and non-carriers were observed in the prevalence of IDC (36% gBRCA2 versus 50% non-carriers, p = 0.085) or CRIB (53% gBRCA2 versus 43% non-carriers p = 0.197) patterns. However, IDC histology was independently associated with bi-allelic BRCA2 alterations (OR 4.3, 95%CI 1.1–16.2) and PTEN homozygous loss (OR 5.2, 95%CI 2.1–13.1). CRIB morphology was also independently associated with bi-allelic BRCA2 alterations (OR 5.6, 95%CI 1.7–19.3). Conclusions: While we found no association between gBRCA2 mutations and IDC or CRIB histologies, bi-allelic BRCA2 loss in primary prostate tumours was significantly associated with both variant morphologies, independently of other clinical-pathologic factors. Highlights: Presence of g BRCA2 mutations was not associated with IDC and CRIB patterns. Results do not support germline BRCA2 testing only based on presence of IDC and/or CRIB. IDC and CRIB patterns were associated with bi-allelic BRCA2 alterations in our study.